Structure-oriented substrate specificity engineering of aldehyde-deformylating oxygenase towards aldehydes carbon chain length. Issue 1 (December 2016) - Bao, Luyao; Li, Jian-Jun; Jia, Chenjun; Li, Mei; Lu, Xuefeng
Abstract Background Aldehyde-deformylating oxygenase (ADO) is an important enzyme involved in the biosynthetic pathway of fatty alk(a/e)nes in cyanobacteria. However, ADO exhibits quite low chain-length specificity with respect to the substrates ranging from C4 to C18 aldehydes, which is not suitable for producing fuels with different properties or different chain lengths. Results Based on the crystal structures of cADOs (cyanobacterial ADO) with substrate analogs bound, some amino acids affecting the substrate specificity of cADO were identified, including the amino acids close to the aldehyde group and the hydrophobic tail of the substrate and those along the substrate channel. Using site-directed mutagenesis, selected amino acids were replaced with bulky ones introducing steric hindrance to the binding pocket via large functional groups. All mutants were overexpressed, purified and kinetically characterized. All mutants, except F87Y, displayed dramatically reduced activity towards C14, 16, 18 aldehydes. Notably, the substrate preferences of some mutants towards different chain-length substrates were enhanced: I24Y forn -heptanal, I27F forn -decanal andn -dodecanal, V28F forn -dodecanal, F87Y forn -decanal, C70F forn -hexanal, A118F forn -butanal, A121F for C4, 6, 7 aldehydes, V184F forn -dodecanal andn -decanal, M193Y for C6–10 aldehydes and L198F for C7–10 aldehydes. The impact of the engineered cADO mutants on the change of the hydrocarbon profile was demonstrated by co-expressing acyl-ACP thioesteraseBTE, fadD and V184F inE. coli, showing thatn -undecane was the main fatty alkane. Conclusions Some amino acids, which can control the chain-length selectivity of substrates of cADO, were identified. The substrate specificities of cADO were successfully changed through structure-guided protein engineering, and some mutants displayed different chain-length preference. The in vivo experiments of V184F in genetically engineeredE. coli proved the importance of engineered cADOs on the distribution of the fatty alkane profile. The results would be helpful for the production of fatty alk(a/e)nes in cyanobacteria with different properties.